Checklist of sea turtles endohelminth in Neotropical region - Werneck, M. R.; Da Silva, R. J. [UNESP] (De Gruyter, 2016)
This paper presents a list of parasites described in sea turtles from the Neotropical region. Through the review of literature the occurrence of 79 taxa of helminthes parasites were observed, mostly consisting of the Phylum Platyhelminthes with 76 species distributed in 14 families and 2 families of the Phylum Nematoda within 3 species. Regarding the parasite records, the most studied host was the green turtle (Chelonia mydas) followed by the hawksbill turtle (Eretmochelys imbricata), olive ridley turtle (Lepidochelys olivacea), loggerhead turtle (Caretta caretta) and leatherback turtle (Dermochelys coriacea). Overall helminths were reported in 12 countries and in the Caribbean Sea region. This checklist is the largest compilation of data on helminths found in sea turtles in the Neotropical region.
Keywords: checklist; helminths; marine turtles; parasites